(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Access to clean drinking water remains a significant public health challenge in low-income urban areas of Pakistan. This project aimed to promote low-cost, home-based water purification methods in an urban slum of Jamshoro using the Community as Partner (CAP) model. Methods: Conducted between January and March 2023, this participatory project engaged ng local stakeholders. A cross-sectional pilot survey was conducted with 33 female residents to assess knowledge, attitudes, and practices (KAP) regarding water purification. Data were collected through structured, interviewer-administered questionnaires. Descriptive analysis identified key trends. Community awareness sessions were conducted following the baseline assessment. Results: The majority of participants (77%) used government-supplied water, with 60% not treating drinking water at home. Barriers included perceived cleanliness (65%), lack of knowledge (25%), and taste alteration (10%). Among those treating water, boiling (19%), cloth filtration (11%), and filtration (10%) were used. About 85% reported family members suffering from waterborne diseases. Post-intervention feedback showed improved community understanding and engagement. Conclusion: The CAP model effectively facilitated stakeholder engagement and health education. Low-cost interventions like boiling and solar disinfection were well received and could be scaled up. This model has promise for enhancing sustainable hygiene practices in underserved communities.